Potential yield of soybean during the ontogeny according to water availability and plant arrangement - Maehler, André Roberto; Pires, João Leonardo Fernandes; Costa, José Antonio; Ferreira, Felipe Gutheil (Pesquisa Agropecuaria Brasileira, 2003)
The quantification of reproductive structures during the ontogeny allows to estimate soybean yield potential (YP), making possible to quantify the effect of environmental factors and management practices on the production and fixation of these structures. This work aimed to determine the effect of water availability and plant arrangement on the YP and its components, during ontogeny of two soybean cultivars. Treatments were two water availability (irrigated and non irrigated), two cultivars (BRS 137 and BRS 138), and three row spacings (20 cm, 40 cm and 20 and 40 cm in skip row). The average YP obtained was of 15,295 kg ha-1 at blooming; 12,325 kg ha-1 during legume formation; 5,508 kg ha-1 at the beginning of grain filling and 4,315 kg ha-1 in maturation phase. The irrigated treatment had higher YP, due to the larger flower and pod production and fixation, more grains per pod and heavier grains, in relation to non irrigated treatment. There was no significant difference among the row spacings tested. The cultivar BRS 137 presented greater YP during the ontogeny than BRS 138, due to less flower abortion, heavier grains and more grains per pod.